PENGARUH SELF EFFICACY TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING PADA CV. ERA DUA RIBU BANGLI - Dewani Agustin; Anak Agung Dwi Widyani; Ni Made Satya Utami (VALUES, 2021)
This study aims to determine the effect of self-efficacy on organizational commitment, self-efficacy on employee performance, organizational commitment to employee performance, and self-efficacy on employee performance through organizational commitment as an intervening variable in CV. Era Dua Ribu Bangli. The population in this study were all employees of CV. Era Dua Ribu Bangli totaling 32 people with the determination of the sample using the census method. The research data collection was carried out by observing and distributing questionnaires. Data were analyzed using the Partial Least Square (PLS) analysis technique to answer the problem formulation with the help of the Smart PLS program. The results of testing the hypothesis show that the variables: 1). Self-efficacy has a positive and significant effect on organizational commitment 2). Self-efficacy has a positive and significant effect on employee performance 3). Organizational commitment has a positive and significant effect on employee performance, and 4). The variable organizational commitment can be an intervening variable between self-efficacy and employee performance.